Editorial: how widespread and serious is non‐alcoholic fatty liver disease in the real world? Authors' reply. Issue 11 (19th May 2020) - Loomba, Rohit; Wong, Robert; Fraysse, Jeremy; Shreay, Sanatan; Li, Suying; Harrison, Stephen; Gordon, Stuart C.
Abstract : LINKED CONTENT This article is linked to Loomba et al and Harris et al papers. To view these articles, visit https://doi.org/10.1111/apt.15679 and https://doi.org/10.1111/apt.15714 .